Intraempreendimentos: uma realidade em organizações estabelecidas - Mendes, Ailson de Sousa (2004)
Many people believe that once the organizations become bigger and bigger, it is very likely it will lose its ability to act as entrepreneur and stimulate innovation. This dissertation has been developed with the major objective of explore how the corporate entrepreneurship - also generally called intrapreneurship - can be a reality in established organizations. The major features of people with an intrapreneur profile is presented as well as compared to 'real entrepreneurs', those who decide to leave the organization to open your own business, and with the corporate manager. It is also explored how innovation and intrapreneuring are connected and assess how a company can use it as source of competitive advantage. Finally, the major criticai success factors are evaluated as well the points that influence the levei of intrapreneurship. Some suggestions are presented to motivate and stimulate intrapreneurship within the boundaries of the firmo